O trem do Quixelô: estudo do desenho de Iguatu (1909-1939) - Sousa, Rodrigo Rolim de (2023)
Iguatu is a city located in the hinterlands of the center-south of the State of Ceará, close to the Jaguaribe River, in a territory historically called Ribeira do Quixelô. In 1909, the Baturité Railway (EFB) arrived at the city, and the region's agricultural production – especially cotton – started to be transported through the railway, directly to the port of Fortaleza. Iguatu becomes one of the main centers of the urban network in the state then. This study examines the local transformations related to the implementation of the railway that happened in Ribeira do Quixelô between the years 1909 and 1939. Initially, as an introduction, a brief history and an overview of the railway network in the State of Ceará are outlined. The first chapter explains the antecedents of implementation of the railway and the process of delimiting the Ribeira do Quixelô and its morphological aspects. Rural properties and urban centers were positioned, revealing the centrality of Iguatu and placing it in the network of paths that supported the land occupation and later the implementation of the railway. The second chapter is about the railroaded urban centers of Ribeira do Quixelô and the urban design and the remnants of the “old architecture” related to the railway system, in particular the stops, stations and railway bridges. These works are testimonies of the urbanization process and the consolidation of Iguatu's hegemony in the Center-South region of the State of Ceará. The third chapter investigates the design of Iguatu before and after the installation of the railway system, between the second half of the 19th century and 1939. During the railwayization period, two stages were identified in the city's urbanization process: one from 1909 till 1924 and another from 1924 till 1939. In conclusion is possible to highlight the centrality of Iguatu and its relevance in the sociospatial processes for the territorial reorganization in Ribeira do Quixelô during the extension of the Baturité Railway (EFB), which transformed the city into a roundabout and brought urban transformations to the city and other railway centers.